2008
DOI: 10.1159/000117311
|View full text |Cite
|
Sign up to set email alerts
|

Do Stem Cells Exist in the Adult Kidney?

Abstract: Adult stem cells exist in many organs and play a critical role in normal cell turnover and the response to injury. The existence of adult stem cells in the mammalian kidney remains controversial. Kidney stem cells have been isolated and characterized by many groups, often with discrepant results. This article will review the current state of knowledge regarding adult kidney stem cells and discuss future directions for kidney stem cell research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 146 publications
(74 reference statements)
0
33
0
Order By: Relevance
“…In organisms such as the skate and freshwater teleost, renal stem cells persist in the adult life and form new nephrons [4,5]. There is increasing debate whether stem cells exist in the adult mammalian kidney and participate in renal regeneration following injury [6,7]. Although great advances have been made in recent years, a major limitation in the field is the lack of definitive markers for identifying stem cells present in the adult mammalian kidney.…”
Section: Introductionmentioning
confidence: 99%
“…In organisms such as the skate and freshwater teleost, renal stem cells persist in the adult life and form new nephrons [4,5]. There is increasing debate whether stem cells exist in the adult mammalian kidney and participate in renal regeneration following injury [6,7]. Although great advances have been made in recent years, a major limitation in the field is the lack of definitive markers for identifying stem cells present in the adult mammalian kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Oct-4 expression has been demonstrated at different locations in the human body like bone marrow, hair follicles, breast, liver, or neural stem cell (Gupta and Rosenberg 2008;Jiang et al 2002;Reyes et al 2002;Yu et al 2006) and now also in nasal polyp cells. Besides Oct-4, Sox2 is one of the transcription factors which is essential for the pluripotent cell development and maintenance of undifferentiated embryonic stem cells (Avilion et al 2003;Nichols et al 1998) and was found in the epithelium of nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…12 Even organs previously considered as post-mitotic, such as the heart or kidney, are now believed to have their own stem cell compartments, which are, however, still poorly understood. 13, 14 …”
Section: Adult Stem Cellsmentioning
confidence: 99%